Ceramide analogue 14S24 selectively recovers perturbed human skin barrier - Vávrová, K; Hrabálek, A; Mac-Mary, S; Humbert, P; Muret, P (The British journal of dermatology, 2007)
BACKGROUND: Topical ceramide application is an effective therapeutic approach in skin disorders with disturbed barrier function, including atopic dermatitis and psoriasis. OBJECTIVES: To evaluate ceramide analogue N-tetracosanoyl-(l)-serine tetradecyl ester (14S24) using a novel ex vivo model. METHODS: Freshly excised human skin was disrupted by lipid extraction, tape stripping and sodium lauryl sulphate (SLS) treatment. Barrier perturbation was evaluated by the measurement of transepidermal water loss (TEWL), skin hydration and the penetration of model compound, theophylline (TH), assessed by microdialysis. The effect of topical 5% 14S24 was compared with a commercial formulation containing a skin lipid mixture (LR) and control formulation with no skin lipids (L). RESULTS: Both LR and 14S24 produced significant recovery of TEWL and TH penetration in extracted and tape-stripped skin with 14S24 being significantly more effective. In SLS-treated skin, 14S24 decreased TEWL but not TH penetration; LR was inactive. L improved skin hydration but not barrier characteristics. Weak correlation between TEWL and TH penetration was observed in extracted and tape-stripped skin but not in SLS-treated skin. CONCLUSIONS: Cutaneous microdialysis can serve as a useful tool for the evaluation of skin barrier recovery by topical formulations ex vivo whereas TEWL may not be an appropriate measure of skin barrier function in such studies. The excellent barrier repair activity of 14S24 could be beneficial in skin disorders with ceramide deficiency.
Keywords: dodecylsíran sodný; preklinické hodnocení léčiv; Solvents; perspiratio insensibilis; theofylin; rozpouštědla; Microdialysis; Adult; Tissue Culture Techniques; dospělí; Ceramides; kůže; Sodium Dodecyl Sulfate; techniky tkáňových kultur; Theophylline; mikrodialýza; lidé; ženské pohlaví; Detergents; Skin; ceramidy; Body Water; Drug Evaluation, Preclinical; Humans; kožní absorpce; Skin Absorption; tělesná voda; Female; Serine; lidé středního věku; Water Loss, Insensible; serin; Middle Aged; detergenty